2020
DOI: 10.18632/aging.103121
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate promotes the proliferation of neural stem/progenitor cells and alleviates Ischemia-reperfusion Injury through PI3K/Akt/FOXO-3a/p27kip1 signaling pathway

Abstract: Stroke is one of the leading causes of death worldwide that also result in long-term disability. Endogenous neural stem/progenitor cells (NSPCs) within subventricular (SVZ) and dentate gyrus (DG) zone, stimulated by cerebral infarction, can promote neural function recovery. However, the proliferation of eNSPCs triggered by ischemia is not enough to induce neural repair, which may contribute to the permanent disability in stroke patients. In this study, our results showed that following the treatment with artes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 42 publications
3
34
0
Order By: Relevance
“…23) Previous studies have shown that ART can alleviate I/R injury after a stroke. 16,17) These findings are consistent with our results. Shao et al used two ART groups (30 mg/kg and 60 mg/kg) and both showed neuroprotective effects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…23) Previous studies have shown that ART can alleviate I/R injury after a stroke. 16,17) These findings are consistent with our results. Shao et al used two ART groups (30 mg/kg and 60 mg/kg) and both showed neuroprotective effects.…”
Section: Discussionsupporting
confidence: 93%
“…16) Zhang et al used three ART groups (50 mg/kg, 150 mg/kg, and 250 mg/kg) and showed that 150 mg/kg was the optimal ART dosage. 17) We designed four ART groups (20 mg/kg, 40 mg/kg, 80 mg/kg, and 160 mg/kg) and all showed neuroprotective effect vs. the vehicle group. Among them, 80 mg/kg was the optimal ART dosage for the rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that PL significantly reduced the expression of PI3K/AKT/mTOR at the protein level, therefore, we believe that PL may exert its cycle arrest and induce cell apoptosis through the PI3K/AKT/mTOR signaling pathway. AKT can promote the phosphorylation of MDM2 to inhibit the degradation of p53 [ 44 ], and AKT can directly inhibit the phosphorylation of p21 and p27 to achieve the purpose of cell cycle arrest [ 45 , 46 ]. In addition, AKT inhibits the phosphorylation of GSK-3β [ 47 ], GSK-3β further induced apoptosis [ 48 ], several researchers have revealed that PL shows its cell cycle arrest and apoptosis by inhibiting PI3K/AKT/mTOR in other cell lines [ 49 – 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whether we can promote the proliferation of endogenous stem cells through some exogenous interventions may also be a novel therapeutic approach. For example, Zhang et al (2020) showed that treatment with artesunate promoted the proliferation of NSPCs via some molecular mechanisms, subsequently reducing the infracted brain volume and alleviating motor function impairment caused by MCAO. Zhuang et al (2012) had undertaken a study to examine the promotive effect of salvianolic acid B (Sal B) on NSPC proliferation and neurogenesis.…”
Section: Discussionmentioning
confidence: 99%